What have we learned from 691 prenatal chromosomal microarrays for ventricular septal defects?. (9th September 2019) - Maya, Idit; Singer, Amihood; Yonath, Hagith; Reches, Adi; Rienstein, Shlomit; Zeligson, Sharon; Ben Shachar, Shay; Sagi‐Dain, Lena
Abstract: Introduction: Ventricular septal defect (VSD) represents the most common type of congenital cardiac anomaly, affecting more than 1 in 300 live births. The objective of this study was to examine the incidence and nature of abnormal chromosomal microarray analysis (CMA) results in a large cohort of pregnancies with VSD. Material and methods: Data acquisition was performed through the Ministry of Health computerized database. All CMA results performed due to VSD during 2013‐2017 were included. The rates of clinically significant CMA results of cases with isolated and non‐isolated VSD were compared with two control populations—a systematic review of 9272 pregnancies and a local cohort of 5541 fetuses with normal ultrasound. Results: Overall, 691 CMA analyses performed due to a sonographic indication of VSD were detected. Of 568 pregnancies with isolated VSD, eight (1.4%) clinically significant copy number variants were detected, a nonsignificant difference compared with low risk pregnancies. Of the 123 pregnancies with non‐isolated VSDs, 18 (14.6%) clinically significant CMA results were detected, a considerably increased risk compared with control pregnancies. Karyotype‐detectable anomalies constituted 12 of the 18 abnormal CMA results in non‐isolated VSD group (66.7%), a significantly higher proportion compared with 2 of 8 (25%) in isolated VSD cohort. Conclusions: The outcomes of our study, representing the largest number of CMA results in pregnancies with VSD, suggest that the rate of abnormal CMA findings in isolated VSD does not differ from pregnancies with normal ultrasound. This observation is true for populations undergoing routine common trisomy screening tests and early sonographic evaluation, as well as widely available non‐invasive prenatal screening. Conversely, CMA analysis yields a high detection rate in pregnancies with non‐isolated VSD. Our results question the recommendation to perform invasive prenatal testing for CMA in pregnancies with isolated VSD.